# How do you solve #3(5j + 2) = 2(3j - 6) #?

##### 1 Answer

Jan 18, 2017

#### Answer:

#### Explanation:

Distribute the brackets on both sides of the equation.

#rArr15j+6=6j-12# Collect terms in j on the left side and numeric values on the right side.

subtract 6j from both sides.

#15j-6j+6=cancel(6j)cancel(-6j)-12#

#rArr9j+6=-12# subtract 6 from both sides.

#9jcancel(+6)cancel(-6)=-12-6#

#rArr9j=-18# To solve for j, divide both sides by 9

#(cancel(9) j)/cancel(9)=(-18)/9#

#rArrj=-2" is the solution"#

#color(blue)"As a check"# substitute j = -2 into the equation and if the left side equals the right side then it is a solution.

#"left side " =3(5xx-2+2)=3(-8)=-24#

#"right side " =2(3xx-2-6)=2(-12)=-24#

#rArrj=-2" is the solution"#